A Decade of Analysis: Household Food Insecurity Among Low-Income Immigrant Children. (January 2018) - Potochnick, Stephanie; Arteaga, Irma
Our study advances literature on immigrant food insecurity by examining whether national-level differences in immigrant and nonimmigrant families' risk of food insecurity persist across time and for different ethnic/racial groups. Using data from the Current Population Survey Food Security Supplement for low-income households with children aged 0 to 17 years, we examine trends (2003-2013) in immigrant and nonimmigrant food insecurity overall and for different ethnic/racial groups. We also assess how immigrant families are faring compared with their nonimmigrant peers in the wake of the Great Recession and its prolonged recovery period. We find that among low-income households with children, noncitizen immigrant households and their U.S.-born household counterparts experience similar levels of food insecurity, while citizen immigrant households demonstrate the lowest levels of food insecurity. Citizen immigrant households, however, appear to have been most affected by the Great Recession and the protective influences of citizenship status do not appear to extend to Hispanic immigrants.